High-power high-brightness solar laser approach for renewable Mg recovery from MgO - Almeida, Joana (2021)
Hydrogen and heat energy from the reaction of magnesium with water can be used for engines and fuel cells. However, at least 4000 K is necessary for magnesium oxide reduction. Ultra high brightness solar-pumped lasers become essential to make this renewable process technology efficient and economically competitive. 2.3 mg/kJ solar laser - induced magnesium production efficiency has been achieved by T. Yabe et al., in 2012, by focusing a 53 W solar laser beam on a mixture of MgO with Si as reducing agent. This result is however far from the 12.1 mg/kJ attained with 2 kW/mm2 CO2 laser beam. To improve substantially the solar laser - induced Mg production efficiency, a simple high-power, high brightness Nd:YAG solar laser pumping approach is proposed. The solar radiation is both collected and concentrated by four Fresnel lenses, and redirected towards a Nd:YAG laser head by four plane folding mirrors. A fused-silica secondary concentrator is used to compress the highly concentrated solar radiation to a laser rod. Optimum pumping conditions and laser resonator parameters are found through ZEMAX